2016
DOI: 10.1371/journal.pone.0147897
|View full text |Cite
|
Sign up to set email alerts
|

BMP-7 Treatment Increases M2 Macrophage Differentiation and Reduces Inflammation and Plaque Formation in Apo E-/- Mice

Abstract: Inflammation plays a fundamental role in the inception and development of atherosclerosis (ATH). Mechanisms of inflammation include the infiltration of monocytes into the injured area and subsequent differentiation into either pro-inflammatory M1 macrophages or anti-inflammatory M2 macrophages. We have previously published data suggesting bone morphogenetic protein-7 (BMP-7) enhances M2 macrophage differentiation and anti-inflammatory cytokine secretion in vitro. In this regard, we hypothesized BMP-7 would inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 35 publications
5
57
0
Order By: Relevance
“…BMP6 regulates expression of inflammatory markers such as IL-6, IL-1β, and nitric oxide synthase in macrophages [7880]. In addition, more recent studies indicate that BMP exposure particularly leads to the M2 or anti-inflammatory phenotype of the macrophages promoting tissue repair [8184]. Microglia are descendants of immature macrophages and are thought to act as macrophages in disease and injury states [85].…”
Section: Discussionmentioning
confidence: 99%
“…BMP6 regulates expression of inflammatory markers such as IL-6, IL-1β, and nitric oxide synthase in macrophages [7880]. In addition, more recent studies indicate that BMP exposure particularly leads to the M2 or anti-inflammatory phenotype of the macrophages promoting tissue repair [8184]. Microglia are descendants of immature macrophages and are thought to act as macrophages in disease and injury states [85].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of various inflammatory diseases, such as atherosclerosis (Brown et al, ), mammary cancer (Movahedi et al, ), brain ischaemia (Garcia‐Bonilla et al, ; Miro‐Mur et al, ), liver injury and fibrosis (Tacke and Zimmermann, ) and skeletal muscle repair after acute damage (Kharraz et al, ), are frequently associated with spatiotemporal dysregulation of Ly6C hi and Ly6C low Mos/Mps. It has been reported that treatment with bone morphogenetic protein‐7 mitigates atherosclerosis by enhancing Mo/Mp differentiation toward Ly6C low cells in ApoE −/− mice (Singla et al, ). Thus, targeting certain Mo/Mp populations may represent a useful therapeutic strategy for inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These pro-inflammatory cytokines include IL-6, MCP-1, and TNF-α (Kleemann et al 2008;Outtz et al 2010;Singla et al 2014). Conversely, M2 macrophages are anti-inflammatory, and aid in the repair of damaged tissue, making them a potential candidate for therapeutic options (Rocher et al 2012;Singla et al 2016). Secreted from M2 macrophages are the anti-inflammatory cytokines IL-10 and IL-1RA, and show an increase in the expression of Arginase-1 enzyme important in reducing harmful nitric oxide production (Kleemann et al 2008;Outtz et al 2010;Singla et al 2014).…”
mentioning
confidence: 99%